Interns and their smartphones: use for clinical practice. Issue 1060 (15th November 2013) - O'Connor, P; Byrne, D; Butt, M; Offiah, G; Lydon, S; Mc Inerney, K; Stewart, Brian; Kerin, M J
Abstract : Purpose of the study: Smartphone use among healthcare professionals has become widespread and will continue to grow in the coming years. Study design: In October 2012, a survey was distributed to 230 interns at two of the national intern training networks in the Republic of Ireland, asking how they used smartphones to carry out their clinical work. Results: It was found that out of 108 interns (47.0% response rate, 108/230), 94.4% (102/108) owned a smartphone. Of those respondents who owned a smartphone, on at least a daily basis for the purposes of work, 83.3% (85/102) made or received phone calls, 87.2% (89/102) sent or received texts, and 41.2% (42/102) sent or received emails on their smartphone. A total of 52.9% (54/102) had used their smartphone to take a work related picture. The most commonly used app was the British National Formulary. It was used daily by 30.4% (31/102) of respondents with a smartphone. The most commonly used website was Wikipedia. It was accessed at least weekly by 38.2% (39/102) of respondents with a smartphone. Conclusions: Smartphones are used by the majority of interns on a daily basis in order to perform their job. As such, there is a need for guidance on how patient information can be safely secured and transmitted using smartphones, their appropriate use, and any restrictions on the use of these devices in certain clinical settings. For interns in particular, advice is needed on the credibility of medical apps and websites.